Spirit, riding free : the adventure begins - Selfors, Suzanne (Spirit riding free, 2017)
"Twelve-year-old Lucky Prescott craves adventure, but as a young lady of society she's only been allowed to experience adventure through books. That is, until one fateful day when Lucky, her father, and her aunt leave their neat-and-tidy city life and travel to their new home out west -- the Wild West. At first Lucky is excited, but during the long train ride to her new hometown of Miradero, she begins to worry. What if she doesn't make any new friends? Everyone in the West rides horses, but she's never been allowed to even sit on one. How can she possibly fit in? Anxious about the future, Lucky looks out the train window and sees a majestic wild stallion. When their eyes meet, she senses a connection. But when the stallion is caught by wranglers, Lucky's heart breaks. And when she next sees the stallion, he's tied to a post, refusing to be "broken"... [W]ill these two free spirits be able to find their place in the West?"--Page [4] of cover.